(untitled) (Patan Pragya, 2021)
Perception of the consumer towards the selection of cosmetic product is influenced by the packaging of the product however empirical research on understanding how visual effects of packaging influence women’ consequent product and brand evaluation is scant. This study examines the buying behavior toward the effect of visual packaging on perceived product’s quality, product’s value, and brand preference. A self-administered questionnaire developed from the literature was used to conduct the response survey in January 2020 on patan area where response of 315 women-participants were received during the survey The empirical results show that attitudes toward visual packaging have the major influence on perception towards product quality and brand preference on buying behavior. Moreover, classic and simple style packaging is popular in Nepalese context. Furthermore, consumers in Lalitpur City were not different than consumers from other cities.